Reframing the Approach to Predatory Journals; Embracing a 'Non-Recommended Journal' Model - Abdullah Khalid Omer (Barw Medical Journal, 2025)
For more than a decade, the academic publishing community has been locked in a battle against “predatory journals.” These are commonly understood as outlets that exploit the open access model by charging fees to authors without providing genuine peer review or editorial services [1]. While this campaign has been well-intentioned, its implementation has been riddled with inconsistencies and collateral damage. It is time to re-evaluate our approach—and a promising alternative has recently been proposed.At the 18th Meeting of the European Association of Science Editors (EASE), Kakamad et al. introduced the concept of the Non-Recommended Journal (NRJ), offering a more nuanced and constructive way to classify questionable journals. Their proposal, outlined in a poster presented at the event, acknowledges a critical truth that the current binary model overlooks: not all low-quality or problematic journals are predatory, and not all accused journals are guilty [2].One of the core issues with the term “predatory” is its lack of a universally accepted definition. Attempts to label journals as predatory can often be subjective and based on flawed or incomplete criteria. This ambiguity has led to wrongful accusations and the potential defamation of emerging or under-resourced journals that are making genuine efforts to improve. Worse still, some well-established journals exhibit questionable practices yet avoid scrutiny simply because they don’t fit the “predatory” mold [3].The NRJ framework reframes the discussion by focusing not on intention, but on recommendation. Rather than asking whether a journal is maliciously exploitative, the NRJ model asks whether a journal meets acceptable standards of transparency, editorial rigor, and academic integrity. Journals that do not meet these standards—whether due to deliberate misconduct or lack of infrastructure can be flagged as “non-recommended” without implying criminality or predation [2].This shift in terminology allows for a more flexible and inclusive way to monitor journal quality. It accounts for the so-called “borderline journals,” which may not be outright deceptive but still fail to uphold scholarly standards. By avoiding the inflammatory label of “predatory,” the NRJ system reduces the risk of reputational harm while still guiding authors, reviewers, and institutions toward better publishing decisions.Moreover, the NRJ approach invites continuous re-evaluation. Journals can move in and out of this category based on demonstrated improvements, providing a growth mindset rather than cementing stigmas. This dynamic classification also encourages more transparent criteria, ideally informed by independent watchdogs or academic associations rather than commercial blacklists.It is time we recognize the complexity of the academic publishing ecosystem and evolve beyond the simplistic predator-prey narrative. The NRJ concept represents a practical, fair, and forward-thinking step in that direction. As the academic world continues to grapple with questions of quality, ethics, and accessibility, such innovations are not just welcome, they are essential.